2018
DOI: 10.1007/s11223-018-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of Pavement Plates to the Positive and Negative Phases of the Friedlander Load

Abstract: The dynamic response of pavement plates to a localized Friedlander load based on the threeparameter foundation model with the account of soil inertia is analyzed. The pavement plate is represented by a thin orthotropic plate of finite dimensions, which can rotate and transfer deformation along the contour. The subgrade is simulated with the Pasternak foundation model, including the inertia soil factor, the localized dynamic load is simulated with the Friedlander decay function allowing for the positive and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In 2018, Alisjahbana et al [4] investigated the dynamic response of an orthotropic concrete plate subjected to the positive and negative phases of blast loading and found that negative phases of the localized blast load an important factor in the dynamic response of the stiffened orthotropic plates. In their study, they found that parameters such as stiffness configuration, location of load, and plate thickness, affect the dynamic response of plates subject to Friedlander blast loads.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Alisjahbana et al [4] investigated the dynamic response of an orthotropic concrete plate subjected to the positive and negative phases of blast loading and found that negative phases of the localized blast load an important factor in the dynamic response of the stiffened orthotropic plates. In their study, they found that parameters such as stiffness configuration, location of load, and plate thickness, affect the dynamic response of plates subject to Friedlander blast loads.…”
Section: Introductionmentioning
confidence: 99%
“…The combined effects of the moving load to the thickness of the rigid roadway pavement as well as the type of soil underneath the rigid roadway pavement to the maximum vertical deflection and the distribution of the stresses within the rigid roadway pavement region were determined in this study. The rigid concrete pavement sitting on elastics Pasternak foundation is modeled by using the Kirchhoff theory of thin plates that can be expressed by [7] (1) where Dx is the flexural rigidity of plate in the x-direction; B is the torsional rigidity of plate, Dy is the flexural rigidity of plate in the y-direction,  is the mass density of plate, h is the thickness of plate,  is the damping ratio of plate, Gs is shear modulus of Pasternak foundation, kf is the stiffness coefficient of Pasternak foundation and f(x,y,t) is the vehicle load.…”
Section: Introductionmentioning
confidence: 99%
“…(4) and(5) is carried out in this section. The generalized solution of the spatial function is defined as the multiplication of the function ( ) and ( ) as follows[10]:…”
mentioning
confidence: 99%